Blood loss and coagulation profile in pregnant and non-pregnant queens undergoing elective ovariohysterectomy. Issue 6 (June 2021) - Fudge, James Mack; Page, Bernie; Mackrell, Amy; Lee, Inhyung; Jeffery, Unity
Objectives: The aims of this study were to determine if there is increased risk of intraoperative bleeding in pregnant cats undergoing elective ovariohysterectomy (OHE), and to compare coagulation in queens in various stages of estrus and pregnancy subjected to elective OHE using a whole-blood viscoelastic assay. Methods: Intraoperative blood loss was compared between non-pregnant and pregnant cats undergoing elective OHE. Viscoelastic evaluations of whole blood drawn pre- and postoperatively were performed using a point-of-care device measuring clot time (CT), clot formation time (CFT), alpha angle, maximum clot formation (MCF), amplitude at 10 and 20 mins (A10 and A20, respectively), and lysis index at 30 and 45 mins after MCF (LI30 and LI45, respectively). Results: One hundred and ninety-three cats underwent OHE by a ventral midline approach. Median blood loss was greater for pregnant cats (2.0 ml, range <0.5–13 ml) than non-pregnant cats (<0.5 ml, range <0.5–15 ml; P <0.0001). Preoperatively, pregnant cats had a shorter median CFT (165 s vs 190.5 s), increased median A10 (31 from 25.5 VCM units) and A20 (38 from 35 VCM units), and a lower median LI45 (99% from 100%) than non-pregnant cats. Postoperatively, A10 and A20 increased, and LI30 and LI45 decreased in both non-pregnant and pregnant queens. In pregnant queens, mean CT also increased postoperatively. Conclusions and relevance: Pregnant cats were relatively hypercoagulable and had an increased rate of clot lysis than non-pregnant cats. Intraoperative blood loss was increased in pregnant vs non-pregnant cats, but no clinically relevant bleeding conditions occurred.